Study on the self-healing behavior and rheological properties of carbonyl iron powder-modified asphalt mastic induced by microwave heating - Zhao, Longwei; Yan, Xuliang; Mi, Shizhong; Gao, Jian; Li, Yongxiang (Frontiers in Built Environment, 2025)
In view of the limited application of large-size absorbing materials in asphalt mixture, this study proposes to use micron-sized carbonyl iron powder as absorbing functional filler to design microwave-responsive asphalt mortar by replacing mineral powder with equal volume. A total of 6 groups of carbonyl iron powder modified asphalt mortars with different replacement ratios were prepared. Through rheological tests and indoor microwave heating tests, the rheological properties and heating healing characteristics of carbonyl iron powder modified asphalt mortars with different replacement ratios were explored. The best replacement ratio was determined by comprehensive thermal-rheological-healing properties. The double-piece healing test was used to explore the enhancement mechanism of carbonyl iron powder on the healing effect of asphalt mortar under microwave induction. The results show that carbonyl iron powder can improve the fluidity, heating characteristics and healing repair ability of modified asphalt mortar. The high temperature fluidity of carbonyl iron powder modified asphalt mortar increases with the increase of replacement ratio, but the high replacement ratio will deteriorate the low temperature performance, and the healing effect and flow state are the best at 50 °C. Through grey correlation analysis, it is concluded that 20% of equal volume replacement is the best replacement ratio, and its heating rate is 1.298 °C/s, which can meet the demand of healing temperature. The instantaneous healing rate (R0) of modified asphalt mortar increased by about 21% after equal volume replacement of 20% mineral powder by carbonyl iron powder. Carbonyl iron powder enhanced the healing effect by improving its flow performance and microwave absorption heating capacity.